Pharmacokinetics and Pharmacodynamics of a Proposed Pegfilgrastim Biosimilar MSB11455 Versus the Reference Pegfilgrastim Neulasta in Healthy Subjects: A Randomized, Double-blind Trial - Lickliter, Jason; Kanceva, Radmila; Vincent, Emmanuelle; Schueler, Armin; Harrison-Moench, Eleanor; Yue, Corinne Seng; Stahl, Michael; Ullmann, Martin; Ghori, Vishal; Griffin, Paul (Clinical therapeutics, 2020)
MSB11455 is a proposed biosimilar to the reference pegfilgrastim (Neulasta®). This pivotal equivalence study (NCT03251248) assessed the pharmacokinetic and pharmacodynamic equivalence of MSB11455 to the reference product. This 2-way, 2-sequence, group-sequential, crossover study was conducted in healthy subjects. Subjects received a single subcutaneous dose of MSB11455 or the reference product (both 6 mg/0.6 mL) on Day 1 of each study period. Pharmacokinetic and pharmacodynamic (absolute neutrophil count; ANC) samples were taken predose and up to day 16 post-dose. Non-compartmental parameters were calculated. Immunogenicity samples were taken pre-dose and up to day 84 after the first dose. Safety was assessed throughout the study. A total of 292 subjects were randomized to therapy and treated; 244 received both treatments. For all primary pharmacokinetic and pharmacodynamic parameters, 90% repeated confidence intervals of geometric means ratio of MSB11455 to the reference product were within the pre-defined equivalence range (80.00%–125.00%) for AUC0-∞ (96.59–112.82); AUC0–last (97.29–113.96), Cmax (97.13–114.99), maximum observed effect on ANC (98.74–102.39), and area under the effect–time curve from time zero to time to last quantifiable concentration (97.30–100.23). Safety, tolerability, and immunogenicity were comparable between treatments. No filgrastim-specific neutralizing antibodies were detected with either treatment sequence. Pharmacokinetic and pharmacodynamic equivalence of MSB11455 and the reference product was shown, with comparable immunogenicity, safety, and tolerability between treatments. The study supports the biosimilarity of MSB11455 to the reference product. ClinicalTrials.gov identifier: NCT03251248. •Neutropenia is a serious hematologic toxicity of myelosuppressive chemotherapy.•Pegfilgrastim stimulates the production of neutrophils and decreases infection risk.•MSB11455 is a proposed biosimilar to the reference pegfilgrastim (Neulasta®).•Pharmacokinetic equivalence of MSB11455 and Neulasta® was demonstrated in this study.•Pharmacodynamic equivalence of MSB11455 and Neulasta® was demonstrated in this study.